Reindeer husbandry in the boreal forest: Sami ecological knowledge or the science of "working with nature" - Roturier, Samuel; Nygard, Jakob; Nutti, Lars-Evert; Astot, Mats-Peter; Roué, Marie (UNESCO, 2017)
Includes bibliography